201Tl Scintigraphy in the Evaluation of Palpable and Nonpalpable Breast Lesions: Correlation with Mammography and Ultrasonography - Vural, G.; Atasever, T.; Özdemir, A.; Öznur, I.; Karabacak, N. I.; Gökçora, N.; Işjk, S.; Ünlü, M. (Nuklearmedizin - NuclearMedicine, 1997)
Aim: Our goal was to determine the clinical usefulness of TI-201 to identify breast cancer in patients with suspicious breast lesions on clinical examination, and/or abnormal radiologic (mammography and/or ultrasonography) findings. Methods: TI-201 scintigraphy were performed in sixty-eight patients with 70 breast abnormalities (51 palpable, 19 nonpalpable) and compared with mammography and ultrasonography (US). Early (15 min) and late (3 h) images of the breasts were obtained following the injection of 111 MBq (3 mCi) of TI-201. Visual and semiquantitative interpretation was performed. Results: Final diagnosis confirmed 52 malignant breast lesions and 18 benign conditions. TI-201 visualized 47 of 52 (90%) overall malignant lesions. Thirty-eight of 40 (95%) palpable and 9 of 12 (75%) nonpalpable breast cancers were detected by TI-201 scintigraphy. The smallest mass lesion detected by TI-201 measured 1.5x1.0 cm. Eleven breast lesions were interpreted as indeterminate by mammography and/or sonography. TI-201 scintigraphy excluded malignancy in 7 of 8 (88%) patients with benign breast lesions interpreted as indeterminate. Five of the 18 (28%) benign breast lesions showed TI-201 uptake. None of the fibroadenoma and fibrocystic changes accumulated TI-201. TI-201 scintigraphy, mammography and ultrasonography showed 90%, 92%, 85% overall sensitivity and 72%, 56%, 61% overall specificity respectively. Twenty-one of the 28 (75%) axillary nodal metastatic sites were also detected by TI-201. In malignant and benign lesions, early and late lesion/contralateral normal side (L/N) ratios were 1.58 ± 0.38 (mean ± SD) and 1.48 ± 0.32 (p >0.05), 1.87 ± 0.65 and 1.34 ± 0.20 (p<0.05) respectively. The mean early and late L/N ratios of malignant and benign groups did not show statistical difference (p>0.05). Conclusion: Overall, TI-201 scintigraphy was the most specific of the three methods and yielded favourable results in palpable breast cancers, while it showed lower sensitivity in nonpalpable cancers and axillary metastases. Combined use of TI-201 scintigraphy with mammography and US seems to be useful in difficult cases, such as dense breasts and indeterminate breast lesions.
Keywords: TI-201; breast cancer; radionuclide imaging